Degradation-damage model application for landslide accumulation stability and reinforcement optimization in Southeast Xizang: a case study - Lv, Guangdong; Li, Wenwei; Wang, Baotian; Zuo, Jinyu; Wang, Jiahui (Frontiers in Earth Science, 2024)
This research develops an elastoplastic damage constitutive model incorporating the strain softening response of common engineering soil materials in southeastern Xizang and leverages it to systematically evaluate and optimize reinforcement solutions for highway-traversing landslide accumulations. Grounded in deterioration mechanics theory, an elastoplastic damage formulation is established to characterize the progressive strength loss and failure evolution mechanics of the soils. Subsequent to model verification and calibration, it is numerically implemented in FLAC3D to simulate the stability conditions of a landslide accumulation affecting planned highway infrastructure in southeastern Xizang. Computed safety factors of 1.25, 1.07 and 1.02 under normal operation, rainfall, and seismic excitation loads, respectively, underscore the inadequacy of intrinsic stability. Consequently, dynamic compaction and chemical grouting reinforcement techniques are parametrically assessed via simulation. An optimal stabilization strategy entailing 6-meter-deep densification at the highway location paired with 10% silica fume enhancement of 66.3% of the landslide area and 50.8% of the soil-bedrock interface is identified to satisfy stability requirements, with augmented safety factors of 1.70, 1.49 and 1.23 for the three loading scenarios. Thereafter, the improved area is methodically minimized to stream-line construction practicality and economics while preserving geotechnical integrity. The integrated modeling outcomes demonstrate the capability of the proposed model in capturing localized incremental damage and the broader efficacy of numerical simulation for stability diagnosis and targeted remediation design of intricate landslides. Continued advancements in constitutive relations development and application are vital to further innovation in geohazard evaluation and infrastructure safety assurance.